P1-S5.08 Attendance at local and national sex-events associated with STD diagnosis, San Francisco, 2010. (10th July 2011) - Bernstein, K; Hjord, H; Marcus, J; Kohn, R; Philip, S
Abstract : Background: A variety of sex-themed events draw crowds from across the USA and provide opportunities for sex partner recruitment, potentially amplifying local sexual networks and complicating disease prevention and control. We examined the frequency of attendance at such events and the association between attendance and incident STD diagnosis among patients visiting a municipal STD clinic. Methods: During 21 September 10–1 November 10, patients seeking services at San Francisco City Clinic were invited to complete a survey about their attendance at local and national events in the prior 12 months, including street fairs, gay pride events, Burning Man, leather events, and circuit parties. Survey results were linked with data from the clinic visit, including self-reported risk behaviours and STD diagnoses. Analyses were stratified by sexual orientation. Events traditionally associated with sex partner recruitment (sex events) were combined. χ 2 and Wilcoxon rank-sum statistics were used to compare patients who attended sex events with all other patients completing the survey. Results: Of the 246 completed surveys, 106 (43.1%) were among heterosexual patients and 140 (56.9%) were among men who have sex with men (MSM). Twenty per cent of heterosexual patients and 47% of MSM patients reported attending a sex event in the prior 12 months. Among heterosexual patients, those attending a sex event were of younger age (median 25 vs 29 years, p=0.014), reported fewer sex partners in the prior 12 months (median 1 vs 2, p=0.021) and were more likely to be at their first visit to the STD clinic (71.4% vs 47.1%, 0.045). There was no association between STD diagnosis and event attendance among heterosexuals. Among MSM, those attending sex events reported more sex partners in the prior 12 months (median 10 vs 5, p=0.019), were more likely to be residents of San Francisco (83.3% vs 66.2%, p=0.021), and were more likely to be diagnosed with chlamydia (15.2% vs 4.1%, p=0.024) or any STD (29.0% vs 14.9%, p=0.045) at that visit. Conclusions: Attendance at sex events was common among patients at an urban STD clinic. Among MSM, attendance was associated with more sex partners and STD diagnosis. The ability of local programs to successfully prevent and control STDs may be complicated by recruitment of new sex partners at such events. Innovative collaborative prevention interventions at sex events and for residents returning from such events should be explored.